Decellularized adipose tissue scaffolds guide hematopoietic differentiation and stimulate vascular regeneration in a hindlimb ischemia model. (July 2021) - Leclerc, Christopher J.; Cooper, Tyler T.; Bell, Gillian I.; Lajoie, Gilles A.; Flynn, Lauren E.; Hess, David A.
Abstract: Cellular therapies to stimulate therapeutic angiogenesis in individuals with critical limb ischemia (CLI) remain under intense investigation. In this context, the efficacy of cell therapy is dependent on the survival, biodistribution, and pro-angiogenic paracrine signaling of the cells transplanted. Hematopoietic progenitor cells (HPC) purified from human umbilical cord blood using high aldehyde dehydrogenase-activity (ALDH hi cells) and expanded ex vivo, represent a heterogeneous mixture of progenitor cells previously shown to support limb revascularization in mouse models of CLI. The objectives of this study were to investigate the utility of bioscaffolds derived from human decellularized adipose tissue (DAT) to guide the differentiation of seeded HPC in vitro and harness the pro-angiogenic capacity of HPC at the site of ischemia after implantation in vivo . Probing whether the DAT scaffolds altered HPC differentiation, label-free quantitative mass spectrometry and flow cytometric phenotype analyses indicated that culturing the HPC on the DAT scaffolds supported their differentiation towards the pro-angiogenic monocyte/macrophage lineage at the expense of megakaryopoiesis. Moreover, implantation of HPC in DAT scaffolds within a unilateral hindlimb ischemia model in NOD/SCID mice increased cell retention at the site of ischemia relative to intramuscular injection, and accelerated the recovery of limb perfusion, improved functional limb use and augmented CD31 + capillary density when compared to DAT implantation alone or saline-injected controls. Collectively, these data indicate that cell-instructive DAT scaffolds can direct therapeutic HPC differentiation towards the monocyte/macrophage lineage and represent a promising delivery platform for improving the efficacy of cell therapies for CLI.